TEACHING AND PROMOTION ON INQUIRYBASED INSTRUCTIONAL MODULE - Chao, Li-Ling; Lin, Chung-Chi; Wang, Wei-Lung (European Scientific Journal, ESJ, 2015)
The purpose of this study is to design two teaching modules that will enable science teachers to teach laboratory course for students to achieve a meaningful and useful learning. We emphasize students’ self-exploration about science. Each module can be modified for students of different grades (7-12 students) and abilities. The modules greatly enhanced the teacher's own understanding of what he/she wishes the laboratory teaching to achieve. The module contained inquiring activities with explicit teaching of the nature of science. At the same time, these activities can promote their learning motivation; let the students have a better understanding of the science concepts by doing the experiments, and to undergo an experience of learning and reflection by themselves. By observing interesting phenomena and practicing the scientific process skills repeatedly, the modules also efficiently inspired students who lack of learning motivation. This study involves the design of two experimental teaching modules dealing with concepts about animal life, plant life, foraging behavior and social behavior. The designed modules are: 1) Ecosphere experimental teaching module: including photosynthesis, respiration and burning; and 2) Animal behavior ecological observation experimental teaching module: including foraging behavior and social behavior.